THE LIMITS OF USAGE CAPACITY REGULATED BY THE NEW CIVIL CODE - Eugen, Chelaru (Anales Universitatis Apulensis Series Jurisprudentia; No 15 (2012): ANNALES UNIVERSITATIS APULENSIS - SERIES JURIPRDENTIA, 2012)
The juridical personality is inherent to humans and it represents the fitness to be subject of legal relations. It is the fundament of civil equality in the sense that any natural person has the capacity of acquiring any right and undertake any obligation, capacity which can be differently fulfilled from one individual to another. The civil equality is not altered by the fact that through law, some categories of persons may be disqualified to conclude juridical documents. The fundament of instituting this incapacity is either the necessity to protect the very person disqualified of the bad consequences of the juridical documents concluded or the general juridical interests. As a consequence, the civil incapacities are subdivided into incapacities of protection and incapacities of punishment. In this paper we shal deal with the legal usage incapacities consisting in depriving an individual of a right, namely the right of concluding a certain juridical document both in person and through a legal delegate. Keywords : juridical personality, civil equality, usage capacity, exercise capacity, civil incapacity, absolute nullity, relative nullity.